2023
DOI: 10.1097/prs.0000000000010616
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Nipple-Sparing Mastectomy: Lessons Learned in 3035 Immediate Implant-based Breast Reconstructions

Abstract: Background: Nipple-sparing mastectomy is commonly performed for breast cancer treatment or prevention. The authors present one of the largest breast reconstruction series in the literature. Methods: A single-institution retrospective review was conducted from 2007 to 2019. Results: The authors’ query identified 3035 implant-based breast reconstructions after nipple-sparing mastectomy, including 2043 direct-to-implant and 992 tissue expander–to-implant reconstructions. The overall major complication rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It has been demonstrated that acellular matrices undergo neo-vascularization and recellularization by host cells ( 19 - 21 ). In breast reconstruction, ADMs are used to enhance skin coverage, particularly after the placement of a silicone implant or tissue expander ( 4 , 22 ). Another goal is to reduce the risk of capsule contracture, a significant complication of implant-based surgeries, leading to a substantial decrease in the long-term cosmetic result ( 23 ).…”
Section: Literature Review Of Tissue- and Bio-engineering Approaches ...mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that acellular matrices undergo neo-vascularization and recellularization by host cells ( 19 - 21 ). In breast reconstruction, ADMs are used to enhance skin coverage, particularly after the placement of a silicone implant or tissue expander ( 4 , 22 ). Another goal is to reduce the risk of capsule contracture, a significant complication of implant-based surgeries, leading to a substantial decrease in the long-term cosmetic result ( 23 ).…”
Section: Literature Review Of Tissue- and Bio-engineering Approaches ...mentioning
confidence: 99%
“…A retrospective review conducted over ten years at the Massachusetts General Hospital included more than 3,000 patients undergoing breast reconstruction ( 4 ). One aspect of their analysis compared the outcomes of pre-pectoral implant reconstruction with ADM-enhanced coverage versus subpectoral techniques, where the implant is placed partially under the muscle.…”
Section: Literature Review Of Tissue- and Bio-engineering Approaches ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is true in face lifts, free flaps, and-as is demonstrated again in this article-implant-based mastectomy reconstruction. The breast program at Massachusetts General Hospital delivers an exceptional article 1 and there is a lot to unpack. The most important concept to understand, is that this is not a randomized clinical trial, and the outcomes reflect the science and art of a highly skilled and experienced team navigating patients through a complex process.…”
mentioning
confidence: 99%
“…Immediate breast reconstruction (IBR) using free flaps after nipple-sparing and skin-reducing mastectomies can provide natural-looking outcomes in a one-step surgical approach, providing several advantages for both the patient and the healthcare system, in a time- and cost-effective way. Indeed, studies show no negative impact on recurrence or patient survival, but better aesthetic outcome, less psychological distress, and lower treatment costs in IBR [ 4 ]. Finally, in the last decade, lymphatic surgery advancements have become extremely popular and have also affected the breast reconstruction journey.…”
mentioning
confidence: 99%